2015
DOI: 10.1186/s12957-015-0451-7
|View full text |Cite
|
Sign up to set email alerts
|

pERK1/2 silencing sensitizes pancreatic cancer BXPC-3 cell to gemcitabine-induced apoptosis via regulating Bax and Bcl-2 expression

Abstract: BackgroundOur previous study has demonstrated that knockdown of activated ERK1/2(pERK1/2) sensitizes pancreatic cancer cells to chemotherapeutic drug gemcitabine (Gem) treatment. However, the details of this survival mechanism remain undefined. It has also shown that Bcl-2 confers resistance and Bax sensitizes to gemcitabine-induced apoptosis in pancreatic cancer cells. Furthermore, the extracellular signaling-regulated kinase (ERK) signaling pathway regulates Bcl-2/Bax expression ratio. We therefore tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…We sought to determine whether FBP1 E4 can restore gemcitabine sensitivity in PDAC cells through inhibition of pERK1/2. In agreement with the findings in the BXPC-3 PDAC cell line (27) and RAS mutation–induced mouse PDAC tumors (29), we found that the mean value of pERK1/2 staining was relatively higher in gemcitabine-treated PDAC patient specimens compared with that in untreated counterparts (Supplementary Fig. S1B and S1C).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We sought to determine whether FBP1 E4 can restore gemcitabine sensitivity in PDAC cells through inhibition of pERK1/2. In agreement with the findings in the BXPC-3 PDAC cell line (27) and RAS mutation–induced mouse PDAC tumors (29), we found that the mean value of pERK1/2 staining was relatively higher in gemcitabine-treated PDAC patient specimens compared with that in untreated counterparts (Supplementary Fig. S1B and S1C).…”
Section: Resultssupporting
confidence: 90%
“…However, it fails to significantly improve the outcome of pancreatic carcinoma patients due to acquisition of chemoresistance in most tumor cells (26). It is well documented that gemcitabine treatment results in activation of the RAS–RAF–MAPK pathway (27). However, the mechanism underlying gemcitabine-induced MAPK activation remains poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, low concentrations of formononetin may significantly promote CNE2 cell proliferation through p-ERK upregulation. This process subsequently modulates the activity of downstream targets, including some members of the bcl-2 protein family (Wang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine belongs to the pyrimidine antineoplastic drugs. Its main metabolites can incorporate into the DNA of cancer cells, followed by breaking the normal function of DNA and thus activating the apoptotic pathway of cancer cells [6,7]. However, gemcitabine resistance is usually seen during the PCa treatment [8,9].…”
Section: Introductionmentioning
confidence: 99%